Lower extremity joint moments during uphill cycling - Caldwell, G. E.; Hagberg, J. M.; McCole, S. D.; Li, L. (Journal of Applied Biomechanics, 1999)
Lower extremity joint moments were investigated in three cycling conditions: level seated, uphill seated and uphill standing. Based on a previous study (Caldwell, Li, McCole, & Hagberg, 1998), it was hypothesized that joint moments in the uphill standing condition would be altered in both magnitude and pattern. Eight national caliber cyclists were filmed while riding their own bicycles mounted to a computerized ergometer. Applied forces were measured with an instrumented pedal, and inverse dynamics were used to calculate joint moments. In the uphill seated condition the joint moments were similar in profile to the level seated but with a modest increase in magnitude. In the uphill standing condition the peak ankle plantarflexor moment was much larger and occurred later in the downstroke than in the seated conditions. The extensor knee moment that marked the first portion of the down-stroke for the seated trials was extended much further into the downstroke while standing, and the subsequent knee flexor moment period was of lower magnitude and shorter duration. These moment changes in the standing condition can be explained by a combination of more forward hip and knee positions, increased magnitude of pedal force, and an altered pedal force vector direction. The data support the notion of an altered contribution of both muscular and non-muscular sources to the applied pedal force. Muscle length estimates and muscle activity data from an earlier study (Li & Caldwell, 1996) support the unique roles of mono-articular muscles for energy generation and bi-articular muscles for balancing of adjacent joint moments in the control of pedal force vector direction.